One piece mathematics board game (1PM3) - Ajol, Tracy Adeline; Robert, Cindy; Joseph, Stefanie Natasha Rich; Awg. Ali, Awang Nasrizal; Gran, Shirley Sinatra; Long, Suffina (Universiti Teknologi MARA, Kedah, 2023)
Mathematics plays a vital role in developing students' cognitive abilities and analytical reasoning. Often, difficulties in solving mathematical problems stem from a limited understanding of fundamental concepts, leading to frustration and disengagement. To address this, the innovative board game called 1PM3 was designed to enhance students' comprehension of arithmetic principles, transforming the learning experience into an enjoyable and low-pressure environment that reduces math anxiety. The 1PM3 board game aligns with Sustainable Development Goal 4.0 by promoting inclusive and equitable quality education through its engaging and effective approach to teaching mathematics. This study aims to investigate the impact of 1PM3 on problem-solving proficiency among 35 Pre-Diploma students who participated in the "Mathtournament 2023" at UiTM Sarawak Branch, Mukah Campus. The game, divided into three mathematical chapters, focuses on functions, simultaneous equations, and formula transformation (Business Mathematics). Data was analysed using thematic analysis, incorporating game observation and surveys to gather comprehensive insights of 1PM3 effectiveness in addressing students’ mathematical learning abilities. The findings of the study indicate a significant improvement in problem-solving skills among participants. The competitive and interactive elements of the game effectively sustain students' interest and motivation throughout the learning process. As a result, 1PM3 emerges as a valuable educational tool for teaching and learning mathematics. As educators continue to explore innovative methods, integrating 1PM3 into mathematics teaching practices can pave the way for a more engaging and effective learning experience for students.